2002
DOI: 10.1038/sj.jhh.1001333
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in black people: pathophysiology and therapeutic aspects

Abstract: Salt sensitivity is regarded as an important contributor to the higher risk of hypertension in black people as compared with whites. This finding is in agreement with a better response to diuretics than to monotherapy with angiotensin-converting enzyme (ACE) inhibitor in black subjects. It is important to remember that the hypotensive effect of ACE inhibitor is augmented in patients on a thiazide diuretic. Moreover, the antihypertensive response to a specific drug varies among black patients. Thus, ACE inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Our previous study of anti-hypertensive medicines utilization pattern about 10 years ago showed that ACEIs and beta blockers were the least frequently prescribed 9. The sparse prescribing of ACEIs was associated with the reported relatively lower reduction of blood pressure by ACEIs in the black population especially as monotherapy 15,16. However, this view was challenged by a number of studies which showed that blood pressure response to ACEIs is probably blind to race but sensitive to patients’ factors such as age, body mass index, high entry/baseline blood pressure levels and severe hypertension due to delay in seeking treatment, presence of co-morbidity such as diabetes mellitus and inequity in the access to functional health care 17,18.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study of anti-hypertensive medicines utilization pattern about 10 years ago showed that ACEIs and beta blockers were the least frequently prescribed 9. The sparse prescribing of ACEIs was associated with the reported relatively lower reduction of blood pressure by ACEIs in the black population especially as monotherapy 15,16. However, this view was challenged by a number of studies which showed that blood pressure response to ACEIs is probably blind to race but sensitive to patients’ factors such as age, body mass index, high entry/baseline blood pressure levels and severe hypertension due to delay in seeking treatment, presence of co-morbidity such as diabetes mellitus and inequity in the access to functional health care 17,18.…”
Section: Introductionmentioning
confidence: 99%
“…Racial differences may also affect response to hypertensive treatment. In general, hypertension in black patients appears more difficult to control, and blacks have an increased CV risk associated with hypertension; [25][26][27][28][29][30][31] there was a significantly higher proportion of blacks in NA than in CA and especially EA. Specifically, black patients are more likely to have lowrenin hypertension and more frequently carry variant genotypes and haplotypes of the beta-1 adrenergic receptor, making them generally less likely to respond to ACE inhibitors and beta blockers, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…17 Another example is the poor immunologic response to vaccination seen in malnourished children. 18,19 Secondly, differences in patient adherence may impact on the effectiveness of an intervention.…”
Section: Do Public Health Interventions In the Guidelines Address A Pmentioning
confidence: 99%